2014
DOI: 10.14295/holos.v14i1.6787
|View full text |Cite
|
Sign up to set email alerts
|

Revisão Da Qualidade De Estudos De Impacto Ambiental De Pequenas Centrais Hidrelétricas

Abstract: RESUMOA matriz elétrica brasileira apoia-se sobre empreendimentos hidrelétricos, com evidente predominância de grandes empreendimentos geradores de energia. Nos últimos anos, as Pequenas Centrais Hidrelétricas (PCHs) têm ganhado destaque dentre os empreendimentos que constituem o parque gerador no país, estimuladas pela perspectiva de um menor nível de conflitos socioambientais em comparação com os grandes empreendimentos. Ocorre que, da mesma forma que grandes usinas, as PCHs apresentam uma gama de impactos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
4
0
7
Order By: Relevance
“…The authors show that the EISs cover impacts on water, air and soil, but do not consider important issues related to the sugarcane industry expansion, such as food security and greenhouse gas emissions. Montaño et al (2014) review the quality of three EISs of small hydro plants and conclude that none of them met the established quality criteria, noting that the studies do not allow to support a conclusion on the environmental viability of the projects, recommending that the competent environmental agency should review its requirements and guidance presented to the proponents.…”
Section: Evaluation Of Eia Document Qualitymentioning
confidence: 99%
“…The authors show that the EISs cover impacts on water, air and soil, but do not consider important issues related to the sugarcane industry expansion, such as food security and greenhouse gas emissions. Montaño et al (2014) review the quality of three EISs of small hydro plants and conclude that none of them met the established quality criteria, noting that the studies do not allow to support a conclusion on the environmental viability of the projects, recommending that the competent environmental agency should review its requirements and guidance presented to the proponents.…”
Section: Evaluation Of Eia Document Qualitymentioning
confidence: 99%
“…Source: Environmental Resources Management 20012.2. Environmental impact statement (eis) checklists EIS quality appraisal, as well as the identification of its gaps, can occur through the application of techniques created by researchers, by national environmental regimentation agencies or through reports developed by experts (APPIAH-OPOKU, 2001;CANELASA et al, 2005;ALMEIDA et al, 2012;MONTAÑO, 2014).…”
Section: Environmental Impact Study Quality Analysis Methodsmentioning
confidence: 99%
“…The study also showed that the checklists were useful tools for analysts and developers concerning the improvement of the quality of the EIS, therefore being a proper tool to assess the EIA in the state of São Paulo. Concerning criteria and sub criteria development, Montaño et al (2014) investigated the quality of environmental impact study in three central hydroelectric facilities, making it possible to compare the EIS and demonstrating HOLOS Environment, v.16 n.1, 2016-P. 40 ISSN:1519 their technical weakness. The Guidance on EIA -EIS Review is an example of the technique organized by environmental regimentation entities.…”
Section: Environmental Impact Study Quality Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vários trabalhos têm focado na avaliação da qualidade dos estudos de impacto ambiental como um indicador de desempenho do processo de avaliação de impacto ambiental, mas a má qualidade de boa parte destes estudos é apontada como um dos principais problemas da aplicação deste instrumento (RAIMUNDO et al, 2012;MONTAÑO et al, 2014).…”
Section: P a G E | 284unclassified